Характеристика физической подготовленности ливанских мальчиков 6–8 лет разных типов телосложения - Делбани, Хасан; Delbani, Hasan (Східноєвропейський національний університет ім. Лесі Українки, 2012)
Определены компоненты телосложения и уровень проявления основных физических способностей детей младшего школьного возраста. Отмечается преобладание в развитии скоростных, силовых, скоростно-силовых качеств у представителей мышечного типа телосложения и значительное отставание дегистивного типа телосложения. Данные особенности должны учитываться при разработке дифференцированного подхода школьников с различным типом телосложения для адекватного подбора физических нагрузок на уроках физической культуры и повышения мотивации к занятиям физическими упражнениями. Certain components of stature and level of expression of the essential physical abilities of children of primary school age. Noted in the prevalence in the development of high-speed, power, speed-strength qualities of representatives muscular body type and a significant lag degistivnogo body type. These features should be considered when developing a differentiated approach students with a different type of body for adequate selection of physical activity on physical education and increasing the motivation to engage in physical exercise. Certain components of stature and level of expression of the essential physical abilities of children of primary school age. Noted in the prevalence in the development of high-speed, power, speed-strength qualities of representatives muscular body type and a significant lag degistivnogo body type. These features should be considered when developing a differentiated approach students with a different type of body for adequate selection of physical activity on physical education and increasing the motivation to engage in physical exercise.
Physical Characteristics Prepared by the Lebanese Boys 6–8 Years Different Body Types
Keywords: физическая подготовленность; тип телосложения; мальчики 6–8 лет; physical fitness; body type; boys 6–8 years